'Feminizing' Saint Augustine's City of God: Sister Veronica, the library and scriptorium at Santo Spirito, Verona. Issue 2 (10th December 2019) - Arthur, Kathleen Giles
Abstract: Augustine's City of God has been studied in a humanist context and the impact of its vernacular translation on women readers has not been considered. This essay presents an Italian codex copied by nun scribe Veronica in 1472 in the Benedictine convent Santo Spirito, Verona. It examines the convent's social history, literary and devotional culture known through a library inventory dating c .1475, extant manuscripts and early printed books. The content and appeal of the library for elementary and advanced readers is analyzed. The active scribal culture is seen through nun scribe Scholastica Maffei who had strong humanist connections and Domicilla Bernabuzi da Faenza who translated a religious treatise for presentation to a mentor, a reflection of humanist practices. Veronica's City of God, follows no known iconographic model and has unique pen and ink miniatures that express tension, emotional conflict, an understanding of Augustine's philosophy, and her role in mediating the text with allegorical imagery for her community. This is the first study of a vernacular copy produced by a nun and shows how women religious read and reacted to Augustine's popular text.